Implications of Recent Changes in Nonmetropolitan America: A Discussion of McGranahan, Hobbs, Nachtigal, and Stephens - Steve Nelson (Journal of Research in Rural Education, 1994)
These four articles portray a disturbing scene. From each of these perspectives, we see that changes to the fundamental social fabric are occurring in divergent ways with generally negative consequences for rural communities. Rural communities are being distressed by political and economic influences over which they have little apparent control. After reviewing the works of both Hobbs (1994) and McGranahan (1994), one would wonder why people choose to live in rural areas at all. Perhaps they are a resilient, adventurous breed that "celebrates adversity?" I don't think so. We need to change the way we think about rural people, places, and policy if we are ever to achieve educational and social goals of quality of life. The implications of these four articles bring three fundamental lessons to my mind.